Irish droughts in newspaper archives: rediscovering forgotten hazards?. (6th June 2017) - Murphy, Conor; Noone, Simon; Duffy, Catriona; Broderick, Ciaran; Matthews, Tom; Wilby, Robert L.
Abstract : Irish newspaper collections are a rich source of information on historical droughts. Following a search of 250 years of such archives, this paper brings to light four newspaper articles describing three drought events that convey the cultural impacts and unusual societal responses to drought in nineteenth century Ireland. Amongst the archives we find two poems from 1806 and 1893, a call to pray for rain in 1887, and a suggestion for weather modification in 1893. These records demonstrate that, contrary to recent experience, Ireland is surprisingly prone to drought.